Paralia (Paplajahan Aksara Bali Asyik): Interactive Multimedia Based on Local Wisdom to Improve Balinese Language Learning Outcomes - Gede Wardana Yasa; Ni Putu Kusuma Widiastuti (Journal of Education Technology, 2025)
Balinese language instruction in elementary schools continues to face challenges related to low student learning outcomes, particularly in learning Balinese script, due to the limited use of innovative and interactive learning media. This condition often results in monotonous learning experiences that reduce students’ interest and engagement. This study aims to develop and evaluate the validity and effectiveness of Paralia (Paplajahan Aksara Bali Asyik), an interactive multimedia learning resource grounded in local wisdom, to improve fifth-grade students’ learning outcomes. The study employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research participants included two content experts, two media experts, three students for individual trials, nine students for small-group trials, and 30 students for effectiveness testing. Data were collected through questionnaires and essay-based tests and analyzed using descriptive quantitative techniques and paired-sample t-tests. The results indicate that the Paralia interactive multimedia achieved very high validity scores from content experts (0.983) and media experts (0.980), as well as very positive responses in individual (95%) and small-group (93.05%) trials. The effectiveness test revealed a statistically significant improvement in students’ learning outcomes after using the interactive multimedia. This study concludes that Paralia interactive multimedia based on local wisdom is valid, feasible, and effective for enhancing elementary students’ learning outcomes in Balinese language instruction, particularly in Balinese script learning.